Sacroiliac luxations in cats: Surgery or conservative treatment? - Ziya Yurtal; Muhammed Enes Altuğ; Cafer Tayer İşler; Mehmet Zeki Yılmaz Deveci; İbrahim Alakuş; Ömer Kırgız; Halil Alakuş; Ufuk Kaya (Revista Científica, 2022)
Sacroiliac luxations constitute an important part of hip fractures. In the treatment phase, a choice should be made between surgical and conservative treatment. Which treatment option will yield more effective results depends on many variable factors. In the present study, some of these factors were mentioned and their effects on treatment and outcomes were evaluated. A total of 61 cats, 26 female and 35 male, of various breeds and ages, were included in the study. The mean age of the cats included in the study was 16 months. The mean weight of the cats was 2.87 kg. Cases were categorized as ages, ≤6, 7-12, and ≥13 months of age. In addition, the success criteria of etiological causes, luxation type, and concomitant traumas on decision and outcomes were evaluated. Conservative treatment was preferred more in all age groups and success rates were higher than those of surgery. Conservative treatment was preferred in both genders, and the recovery rate was higher in males than that in females. Regardless of the cause of the trauma, more conservative treatment was preferred, and the rate of good recovery was higher in high-rise falls. Even if there was traumatic injury in addition to sacroiliac luxation, conservative treatment was preferred and the rate of good recovery was higher in cases without concomitant traumatic injury. As a result; age, gender, luxation type and concomitant traumatic injury were not statistically significant on treatment choice. However, good recovery was statistically significant in cases without concomitant traumatic injury.